2009
DOI: 10.1097/brs.0b013e3181a3c18d
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Oxygen-Ozone Therapy in the Treatment of Acute Back Pain With Lumbar Disc Herniation

Abstract: Treatment of LBP and sciatica is a major concern. Although the natural history of acute LBP is often self-limiting, conservative therapies are not always effective; in such cases, O2O3 intramuscular lumbar paravertebral injections, which are minimally invasive, seem to safely and effectively relieve pain, as well as reduce both disability and the intake of analgesic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 39 publications
4
71
0
4
Order By: Relevance
“…This implies that ozone Neucleoplasty is certainly much more effective than the physiotherapy treatment. It is worth to mention here that the significant efficacy of ozone Neucleoplasty of our study is in very close conformity with the results of randomised controlled trials presented by Paoloni et al (24) . Paoloni et al (24) have found that about 61 % of patients undergoing ozone neucleoplasty experienced complete pain relief.…”
Section: Analysis and Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This implies that ozone Neucleoplasty is certainly much more effective than the physiotherapy treatment. It is worth to mention here that the significant efficacy of ozone Neucleoplasty of our study is in very close conformity with the results of randomised controlled trials presented by Paoloni et al (24) . Paoloni et al (24) have found that about 61 % of patients undergoing ozone neucleoplasty experienced complete pain relief.…”
Section: Analysis and Resultssupporting
confidence: 75%
“…It is worth to mention here that the significant efficacy of ozone Neucleoplasty of our study is in very close conformity with the results of randomised controlled trials presented by Paoloni et al (24) . Paoloni et al (24) have found that about 61 % of patients undergoing ozone neucleoplasty experienced complete pain relief. However, similar studies carried out by Zambello et al (25) , Bonetti et al (26) and Gallucci et al (27) claim higher success of the ozone based treatment.…”
Section: Analysis and Resultssupporting
confidence: 75%
“…In medical evaluations made during 6 months, the application of ozone-oxygen mixtures in paraspinal muscles induced pain remission in 61% of patients with lumbar disc herniation who did not respond to a conservative treatment (5). Coinciding with these fi ndings, this study found a signifi cant reduction in pain intensity associated to long-term application of ozone.…”
Section: Discussionsupporting
confidence: 53%
“…Las hernias discales en diferentes sectores de la columna se considera como la patología que ocasiona el mayor índice de ausentismo laboral, se calcula que 8 de cada 10 personas sufrirá a lo largo de su vida algún episodio de dolor lumbar debido a esta patología 10 . El tratamiento con Ozono, es una novedosa terapia de gran utilidad en múltiples patologías, siendo las discopatías (hernias discales) una de la entidades en donde se ha evidenciado mayor utilidad, especialmente a nivel de la columna lumbar, técnica que se fundamenta en la administración de ozono en la musculatura paravertebral contigua al sitio de la lesión y /o en la emergencia de las raíces nerviosas de los nervios raquídeos que formarán el nervio ciático, infiltrando el compartimiento del psoas o espacio de Bonitot, siguiendo la técnica de Capdevilla o Nizora modificado, con lo cual se logra bloquear y reducir el dolor y la sintomatología propia del padecimiento, producto de la comprensión (identación) raquimedular o de raíces nerviosas, reduciendo el material herniado por mecanismos ya explicados anteriormente, cesando el efecto mecánico compresivo 7,[11][12][13][14] . Los efectos del ozono inyectado en la musculatura paravertebral han sido estudiados y respaldados por varios estudios fisiológicos efectuados en Italia por el Dr. Velio Bocci y por otros investigadores en el área 2,15,16 .…”
Section: Discussionunclassified